Literacy: A Way Forward for Quality Education in Nigeria - Usman, Yau.; Isyaku, Mohammed; Isah, A. Tilde (Kashere Journal of Education, 2022)
This paper examines the assessment of literacy as a way forward for quality primary education in Nigeria. Literacy is a life-blood of an individual skills, knowledge, attitude and potentialities. Therefore, assessment in teaching and learning of English gives the teacher the evaluative picture of students’ linguistic background, language competency and the needs of the learner. moreover, the paper posits that multiple of assessments in reading and writing improve students’ level of proficiency in mastering the language. The paper also examines some types of assessment which gives the language teacher an advantage of choice of testing a particular skill be applied in teaching and learning of the basic language skills. However, the paper discussed the purpose of assessment in relation to literacy.